Technology, people, and management working together: A new way for sustainable airport operations - Bakay, Nilayda (Cognitive Sustainability, 2025)
This paper revisits the Technology–People–Management (TPM) framework for sustainable airport operations and strengthens its scientific grounding through a clearer theoretical foundation, transparent bibliometric methodology, and policy-oriented interpretation. A systematic review of fifty-one peer-reviewed articles published between 2010 and 2025 is complemented by keyword co-occurrence analysis to elucidate interdependencies among technology, human factors, and managerial practices. The study interprets these findings through socio-technical systems theory and innovation diffusion perspectives, and aligns them with strategic aviation roadmaps, including the ICAO Global Air Navigation Plan and the SESAR ATM Master Plan. Methodological rigor is enhanced by explicit criteria for keyword normalization, clustering parameters, and robustness checks, while discussion moves beyond description to analyze causal mechanisms that connect the three TPM components. The paper translates results into practical implications for regulators, air navigation service providers, and technology developers, and proposes a research agenda to address underexplored areas such as human–AI teaming, real-time machine learning in operations, and governance for data interoperability.